Eliminating Lightning‐Rod Effect of Lithium Anodes via Sine‐Wave Analogous MXene Layers. Issue 36 (7th August 2022) - Gu, Jianan; Chen, Hao; Shi, Yu; Cao, Zhenjiang; Du, Zhiguo; Li, Bin; Yang, Shubin
Abstract: Lithium metal anodes are regarded as the most promising candidate for rechargeable lithium‐based batteries, but uncontrollable Li dendrites hinder further applications. Here, sine‐wave analogous MXene (Ti3 C2 Tx ) (SWA‐MXene) layers are produced by spreading aqueous MXene dispersion onto the sectional surface of a metallic coil and subsequently drying at room temperature. COMSOL Multiphysics simulations demonstrate that the low curvature in SWA‐MXene layers homogenizes the distributions of lithium ions and electric field, efficiently eliminating the lightning‐rod effect on the surface of aligned electrodes in the process of Li deposition. As a result, the flexible SWA‐MXene layers show a low overpotential for lithium nucleation (≈13.5 mV at 0.05 mA cm −2 ) and deep plating–stripping capacities up to 40 mAh cm −2, as well as a long cycle life up to 1250 h. Full cells consisting of a SWA‐MXene–Li anode and a LiFePO4 cathode also exhibit a durable cycle life up to 420 cycles at 1088 mA g −1 . Abstract : Special sine‐wave analogous MXene (Ti3 C2 Tx ) (SWA‐MXene) layers are designed with low curvature, homogenizing the distribution of lithium ions and electric field, efficiently eliminating the lightning‐rod effect on the surface of aligned electrodes. The flexible SWA‐MXene‐Li anodes show a long cycle life of up to 1250 h and deep plating–stripping capacities up to 40 mAh cm −2 .